DERIVATIONAL AND INFLECTIONAL PREFIXES AND SUFFIXES IN BATUSESA DIALECT OF BALINESE: A DESCRIPTIVE STUDY - Ariani, N.K. (International Journal of Language and Literature, 2017)
This study was designed in the form of descriptive qualitative study with the aim at describing the prefixes and suffixes in Batusesa Dialect of Balinese which belong to derivational and inflectional morpheme. The techniques used to collect the data were observation, recording and interview technique. In this study, there were three informants chosen. The results of this study show that there are four kinds of prefixes found in Batusesa Dialect, namely {n-}, {me-}, {pe-}, and {a-} and five kinds of suffixes namely {-ang}, {-nә}, {-in}, {-an} and {-ә}. There are three kinds of prefixes and one kind of suffixes which belong to derivational morpheme, namely {n-}, {me-}, {pe-}, and {-ang}. Moreover there are three kinds of inflectional prefixes namely {n-}, {me-}, and {a-} and four kinds of suffixes which belong to inflectional morpheme, namely {-nә}, {-in}, {-an} and {-ә}. There were some grammatical functions of prefixes and suffixes in Batusesa dialect of Balinese, namely affix forming verbal, affix forming nominal, affix forming numeral, affix forming adjective, and affix forming adverb, activizer and passivizer.